PENGGUNAAN SLUDGE SEBAGAI PAKAN CALON INDUK IKAN NILA MERAH (Oreochromis sp.) - Rustidja Rustidja (Universitas Gadjah Mada, 2003)
The aim of study was to know the effect of sludge in the ration on the gonadal growth of Oreochromis sp. broodstock. Experimental design used in this experiment was completely Randomized Design. The broodstocks were fed with the ration containing 0-40% of sludge, or with a commercial fish feed as a control.The results were not significantly differences between the treatment in all parameters. The sludge in ration ranging from 0 to 40% resulted the level of gonadal maturation of 4, 6, 7, dan 9. The value of Gonadal Maturation Index on 0,96 to 3,98 % and the control group on 1,75 %. The specific growth rate of broodstock fed with the ration ranged from 1,1 to 1,62 Bw/day and that of the development of gonadal control group was 1,97. The survival rate were variated between 14,29 to 100% and that of the development of gonadal control group is 71,43%. The ration containing 40% sludge is the most suitable feed for maturation in Oreochromis.